The role of vascular endothelial growth factor (VEGF) in pathogenesis of diabetic retinopathy - Urban, Beata; Peczyńska, Jadwiga (Klinika Oczna / Acta Ophthalmologica Polonica, 2003)
The authors present the role of VEGF in microaneurysm formation, blood-retinal barrier breakdown, development of capillary nonperfusion and retinal neovascularization in pathogenesis of diabetic retinopathy. Inhibitors of VEGF in treatment of diabetic retinopathy are presented.